Efficacy of auricular point-vagus nerve stimulation in adolescent insomnia patients and the brain function regulation mechanisms: a study protocol for an experimental, randomized, controlled clinical trial - He, Wei; Guan, Lu; Jiang, Yuhong; Guo, Zi; Shao, Xiaomei; Fang, Jianqiao; Fang, Junfan; Du, Junying (Frontiers in Neurology, 2025)
BackgroundAdolescent insomnia is a prevalent issue with significant implications for mental and physical well-being. Given the increasing incidence of sleep disorders, there is an urgent need for safe and efficient treatment modalities, particularly non-pharmacological interventions. Auricular point therapy, a prominent element of acupuncture in China, is often employed to address insomnia. However, there remains a lack of research on the efficacy of auricular point-vagus nerve stimulation in managing insomnia among teenagers. To evaluate the efficacy of this interventions and explore the regulatory mechanisms of brain function, a randomized trial is planned.Methods/designThis trial is a single-center, single-blind, randomized controlled study. A total of 174 adolescent patients with insomnia will be randomly assigned to either the treatment or control groups. Over a period of 4 weeks, patients in the experimental group will undergo bilateral auricular point-vagus nerve stimulation, while those in the control group will receive bilateral non-auricular acupoint-vagus nerve stimulation. Data collection will occur at baseline, 1 week into the intervention, 4 weeks post-treatment initiation, and 4 weeks post-treatment completion. The primary outcome measures will include the Pittsburgh Sleep Quality Index (PSQI), Adolescent Sleep Hygiene Habits Scale (ASHS), and Adolescent Sleep Assessment Questionnaire (DSM). Secondary outcome measures encompass the Self-Assessment Scale for Anxiety (SAS), Self-Depression Scale (SDS), Quality of Life Scale (SF-36), and Autonomic Composite Score (COMPASS-31). Other indicators will involve the use of functional magnetic resonance imaging (fMRI), heart rate variability (HRV), and polysomnography (PSG).DiscussionThe findings of this study will provide strong support for the use of auricular-vagus nerve stimulation as a safe and effective non-pharmacological intervention for insomnia. This approach will offer advantages over medication by mitigating the risks of addiction and adverse effects associated with prolonged drug therapy. Furthermore, the results will align with prior research that underscores the positive impact of auricular acupuncture point stimulation on enhancing sleep quality.Clinical trial registrationhttps://www.chictr.org.cn, ChiCTR2400087889.